Mechanistic and Kinetic Study of Allyl Alcohol Oxidation Using Quinaldinium Chlorochromate in Acetic Acid Medium - Sekar, K. G.; Palanivel, V. (Recent Developments in Chemistry and Biochemistry Research Vol. 10, 2025)
Quinaldinium chlorochromate is one of the mild oxidants of chromium (VI) compound. This oxidant is used to oxidize the allyl alcohol in aqueous acetic acid medium. The reaction shows first order with respect to quinaldinium chlorochromate and hydrogen ion concentration. It was found to be fractional with respect to allyl alcohol. The reaction rate decreases as the dielectric constant of the medium decreases. The rate of the reaction has a negligible effect on the increase of ionic strength. The reaction does not induce the polymerization of acrylonitrile. The thermodynamic and activation parameters have been calculated using Eyring’s equation. On the basis of experimental facts, a plausible mechanism has been proposed and a suitable rate law is derived.